Trapped Rydberg ions: A new platform for quantum information processing - Mokhberi, Arezoo; Hennrich, Markus; Schmidt-Kaler, Ferdinand (Academic Press Inc., 2020)
In this chapter, we present an overview of experiments with trapped Rydberg ions and outline the advantages and challenges of developing applications of this new platform for quantum computing, sensing, and simulation. Trapped Rydberg ions feature several important properties, unique in their combination: they are tightly bound in a harmonic potential of a Paul trap, in which their internal and external degrees of freedom can be controlled in a precise fashion. High fidelity state preparation of both internal and motional states of the ions has been demonstrated, and the internal states have been employed to store and manipulate qubit information. Furthermore, strong dipolar interactions can be realized between ions in Rydberg states and be explored for investigating correlated many body systems. By laser coupling to Rydberg states, the polarizability of the ions can be both enhanced and tuned. This can be used to control the interactions with the trapping fields in a Paul trap as well as dipolar interactions between the ions. Thus, trapped Rydberg ions present an attractive alternative for fast entangling operations as compared to those mediated by normal modes of trapped ions, which are advantageous for a future quantum computer or a quantum simulator.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Quantum information processing; Quantum simulation; Rydberg states; Trapped ions